T1, T2 Mapping and Extracellular Volume Fraction (ECV): Application, Value and Further Perspectives in Myocardial Inflammation and Cardiomyopathies - Roller, F. C.; Harth, S.; Schneider, C.; Krombach, G. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Cardiac magnetic resonance imaging (CMRI) is a versatile diagnostic tool. One of its main advantages is the possibility of tissue characterization. T1-weighted images for scar and T2-weighted images for edema visualization are key methods for tissue characterization. Otherwise these sequences are strongly limited for the detection of diffuse myocardial pathologies. Recently, rapid technical innovations have generated new techniques. T1, T2 mapping and evaluation of the extracellular volume fraction (ECV) allow quantification of diffuse myocardial pathologies and showed great potential in the visualization of fibrosis, edema, amyloid, iron overload and lipid. In the future these techniques might enable the detection of early cardiac involvement, even act as a prognosticator. Moreover, therapy monitoring and follow-up might be possible due to versatile parameter quantification with these new techniques.Key points:• CMR allows for tissue characterization via T1- and T2-weighted sequences.• In cases of diffuse, global myocardial pathologies, correct image interpretation with traditional CMR sequences might be difficult. • T1, T2 mapping and ECV can quantify diffuse, global myocardial pathologies.• Alterations of myocardial T1 and T2 relaxation times occur in various myocardial diseases (e. g. acute myocarditis).• In the future mapping might act as a prognosticator or therapy monitoring tool.Citation Format:• Roller FC, Harth S, Schneider C et al. T1, T2 Mapping and Extracellular Volume Fraction (ECV): Application, Value and Further Perspectives in Myocardial Inflammation and Cardiomyopathies. Fortschr Röntgenstr 2015; 187: 760 – 770
Keywords: cardiac; MR imaging; amyloidosis; inflammation; technical aspects